Derived Neutrophil-to-Lymphocyte Ratio Predicts Pathological Complete Response to Neoadjuvant Chemotherapy in Breast Cancer - Ocaña, Alberto; Chacón, Jose Ignacio; Calvo, Lourdes; Antón, Antonio; Mansutti, Mauro; Albanell, Joan; Martínez, María Teresa; Lahuerta, Ainhara; Bisagni, Giancarlo; Bermejo, Begoña; Semiglazov, Vladimir; Thill, Marc; et al. (Frontiers in Oncology, 2022)
Background Derived neutrophil-to-lymphocyte ratio (dNLR) is a biomarker associated with clinical outcome in breast cancer (BC). We analyzed the association of dNLR with pathological complete response (pCR) in triple-negative BC (TNBC) patients receiving neoadjuvant chemotherapy (CT). Methods This is a retrospective analysis of two randomized studies involving early stage/locally advanced TNBC patients receiving anthracycline/taxane-based CT+/−carboplatin (GEICAM/2006-03) or nab-paclitaxel/paclitaxel followed by anthracycline regimen (ETNA). dNLR was calculated as the ratio of neutrophils to the difference between total leukocytes and neutrophils in peripheral blood before CT (baseline) and at the end of treatment (EOT). Logistic regression analyses were used to explore dNLR association with pCR. Results In total, 308 TNBC patients were analyzed, 216 from ETNA and 92 from GEICAM/2006-03. Baseline median dNLR was 1.61 (interquartile range (IQR): 1.25–2.04) and at EOT 1.53 (IQR: 0.96–2.22). Baseline dNLR showed positive correlation with increased tumor size (p-value = 1e−04). High baseline dNLR, as continuous variable or using median cutoff, was associated with lower likelihood of pCR in univariate analysis. High EOT dNLR as continuous variable or using quartiles was also associated with lower pCR rate in uni- and multivariate analyses. Conclusions High baseline and EOT dNLR correlates with lower benefit from neoadjuvant CT in TNBC.